SCIENTIFIC AND THEORETICAL BASIS OF DEVELOPMENT OF LEARNING AND PRACTICAL SKILLS OF STUDENTS IN NATURAL SCIENCE EDUCATION - HASANOVA SEVARA GHYOSIDDINOVNA (The Bioscan, 2025)
Arousing students' interest in a certain type of activity in the teaching of natural sciences, increasing their internal need to master educational materials, as well as creating conditions for them to acquire practical activity skills, is an effective way to implement this activity. and the development of tools and theoretical foundations is one of the urgent issues waiting for its solution in the field of education. In this article, the scientific and theoretical basis of the development of students' learning and practical activity skills in natural science education of general education schools is highlighted, and the students' learning and practical activity skills opinions, proposals and recommendations on the organization of educational processes aimed at development, approaches to the development of students' practical skills, as well as the types and stages of the development of learning and practical skills.